(3QSGdI aj bhd GdUhajI ef YQa GdbOQ abO dMOs - (3GdMSjf Hf YHO Gddg Hf GdMSf Hf Ydj Hf SjfG , CHh Ydj GdnHrdNqj Ke GdoHNGQqj GdeYQha HGHf SjfG, (B427 (3g`s
(3ChdgG (B:s
(3SCd HYV GdfGS GdTjN GdQFjS CHG Ydi Hf SjfG Yf eYfi bhd GdUhajI ef YQa SQ GdbOQ abO dMO abGd ai LhGHg Cf gPg GdeSFdI ajgG COfi ZehVI hgj ef GdeSGFd GdJi dG JOhf s
(3BNQgG (B:s
(3CdG JQi Cf GdeMehd ef GdbjOjf LejYkG dG jWGb Med eG jQJcHg ef GdaGA hjNJd dfXGe CMhGd GdYGde dSHH GdeJMed Yf GdbjOjf hGddg CYde hGMce s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B241s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg , JQeje s
Keywords: (3GdJUha hGdBOGH GdTQYjIs